Exploring the Potential of Virtual Reality in Eating Disorder Treatment - Grywińska, Weronika Barbara; Okońska , Aleksandra; Kozakiewicz , Julia; Kościelecki , Kamil; Kalisz, Agnieszka; Skorulska , Iwona; Mączewska, Klaudia; Długozima , Patrycja; Grzeszczuk , Paulina; Głowacka , Aleksandra (Quality in Sport, 2025)
Abstract Introduction: Eating disorders (EDs) are complex mental health conditions with significant treatment barriers, including stigma and limited access to care. Virtual reality (VR) offers a novel approach by providing immersive, controlled environments for addressing body image concerns and maladaptive eating behaviours. This review explores VR’s potential in ED treatment based on recent research. Methods: A literature review was conducted using PubMed, Google Scholar, and Web of Science, focusing on studies from the past five years that examined VR as a treatment tool. Clinical outcomes, intervention types, and methodologies were analysed. Summary of Findings: VR has shown promise in reducing body dissatisfaction, fear of weight gain, and binge eating behaviours. Studies using personalized avatars, attentional bias training, and exposure therapy demonstrated improvements in body image perception, anxiety reduction, and coping skills. VR-enhanced cognitive behavioural therapy (VR-CBT) was particularly effective for bulimia nervosa and binge eating disorder. Conclusions: VR is an effective, accessible tool for ED treatment, offering safe and engaging therapeutic experiences. While promising, further research is needed to refine treatment protocols and enhance personalization. As technology advances, VR has the potential to bridge treatment gaps and improve ED recovery outcomes.